Electrochemical and ellipsometric data related to the formation of soluble silver (I) during the potentiodynamic polarization of polycrystalline silver in basic solutions - Zerbino, Jorge Omar (1985)
Soluble Ag(I) species is formed in the early stages of voltammetric silver electrooxidation in 0.1 M NaOH and 0.1 M NaOH + 1 M NaClO4 solutions at 25°C, as demonstrated by the rotating ring-disc technique. This result allows a reasonable interpretation of ellipsometric data obtained for the anodization of silver under different voltammetric conditions. Correspondingly, two anodic layers of different optical constants are electroformed. The hydrous Ag(I) oxide layer behaves as a porous structure with an average thickness of about 2.5 times greater than that of the anhydrous oxide.